Evaluation of Photoswitching Properties for Hockey Stick-Shaped Mesogens Bearing Azo Benzene Moieties - Sunil, B. N; Monika, M.; Shanker, Govindaswamy; Hegde, Gurumurthy; Prasad, Veena (Frontiers in Physics, 2021)
In this paper, we report the photoresponsive behaviour of hockey stick-shaped mesogens bearing azo wing with different terminal alkoxy chains at one terminal end. Except for the compound E16 which exhibits SmC along with nematic phase, all other mentioned compounds exhibit nematic phase. Influence of chain length on the photophysical properties investigated using UV-Vis spectroscopy. These diazo compounds exhibit the indistinguishable thermal back relaxation time and these results envisage the effect of orientation of molecules on the photoisomerization. The reversible trans (E) - cis (Z) isomerization time for these compounds investigated by varying the intensity of illuminated UV light. Spectroscopic study of the solid sample using guest-host mixture also studied and the compilation of results forecasts these mesogens as ideal candidates for optical storage devices.